International parallels in leukaemia and diabetes epidemiology. Issue 1 (7th January 2004) - Feltbower, R G; McKinney, P A; Greaves, M F; Parslow, R C; Bodansky, H J
Abstract : Acute lymphoblastic leukaemia (ALL) and type 1 diabetes have an environmental aetiology and common epidemiological features. Incidence rates and national characteristics of both conditions were investigated in 40 countries worldwide. There was a significant positive correlation between diseases. Markers of wealth and affluence were significantly associated with high incidence.